Modest Impact on Risk for Autism Spectrum Disorder of Rare Copy Number Variants at 15q11.2, Specifically Breakpoints 1 to 2. Issue 3 (12th May 2014) - Chaste, Pauline; Sanders, Stephan J.; Mohan, Kommu N.; Klei, Lambertus; Song, Youeun; Murtha, Michael T.; Hus, Vanessa; Lowe, Jennifer K.; Willsey, A. Jeremy; Moreno‐De‐Luca, Daniel; Yu, Timothy W.; Fombonne, Eric; et al.
<x xml:space="preserve">Abstract</x> The proximal region of chromosome 15 is one of the genomic hotspots for copy number variants (CNVs). Among the rearrangements observed in this region, CNVs from the interval between the common breakpoints 1 and 2 (BP1 and BP2) have been reported cosegregating with autism spectrum disorder (ASD). Although evidence supporting an association between BP1‐BP2 CNVs and autism accumulates, the magnitude of the effect of BP1‐BP2 CNVs remains elusive, posing a great challenge to recurrence‐risk counseling. To gain further insight into their pathogenicity for ASD, we estimated the penetrance of the BP1‐BP2 CNVs for ASD as well as their effects on ASD‐related phenotypes in a well‐characterized ASD sample (n = 2525 families). Transmission disequilibrium test revealed significant preferential transmission only for the duplicated chromosome in probands (20T:9NT). The penetrance of the BP1‐BP2 CNVs for ASD was low, conferring additional risks of 0.3% (deletion) and 0.8% (duplication). Stepwise regression analyses suggest a greater effect of the CNVs on ASD‐related phenotype in males and when maternally inherited. Taken together, the results are consistent with BP1‐BP2 CNVs as risk factors for autism. However, their effect is modest, more akin to that seen for common variants. To be consistent with the current American College of Medical Genetics guidelines for interpretation of postnatal CNV, the BP1‐BP2 deletion and duplication CNVs would probably best be classified as variants of uncertain significance (VOUS): they appear to have an impact on risk, but one so modest that these CNVs do not merit pathogenic status. Autism Res2014, 7: 355–362. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.